Pendampingan Penyusunan Perencanaan Manajemen Strategis dan Aksi Pengembangan SMK Menjadi Pusat Keunggulan - Zaenab Hanim; Harliansyah; Metta Virya Monica; Hana Yulia; Lorensius Lorensius; M. Rajib Bustami (Communio: Jurnal Pengabdian Kepada Masyarakat, 2022)
This assistance aims to help solve various problems that exist in schools, in relation to the efforts of vocational high schools to become centers of excellence so that they can produce graduates who are competent in their fields. In general, this assistance is useful for providing knowledge, technique, and art in formulating school strategic planning, so as to develop excellent school programs; and provide skills to school principals in mastering: (1) techniques for analyzing needs optimally in developing excellent school programs; (2) The technique of formulating a clear vision, mission, goals, and objectives in developing the school's flagship program; (3) The technique of formulating a superior program structure to become a center of excellence in accordance with local wisdom; (4) The technique of conducting a SWOT analysis of the capabilities possessed in developing the school's flagship program; (5) Techniques for developing superior programs based on strategic planning. Based on this, it can be concluded that this activity can contribute to (1) Participants having insight into the field of strategic issues in the field of education as a process of preparing and developing school programs in order to improve the quality of education so that it can become a central vocational high school of excellence; (2) Participants are able to formulate and develop school programs based on strategic planning oriented to life skills, and (3) Participants are able to develop their potential as a transformative leader in order to coordinate in achieving school programs in a synergistic and integrated manner.